Startegi Pengorganisasian Adaptif Di MTs Almahrus Mabar Hilir Kecamatan Medan Deli Kota Medan - Muhammad Farhan Khairuman; Nashrul Syakur Chaniago (Universitas Pakuan, 2026)
ADAPTIVE ORGANIZING STRATEGY AT MTS ALMAHRUS MABAR HILIR, MEDAN DELI DISTRICT, MEDAN CITY This study aims to analyze the adaptive organizing strategy at MTs Al-Mahrus Mabar Hilir, Medan Deli District, Medan City. The research used a qualitative approach. Data collection techniques were conducted through interviews, observations, and documentation. The results showed that the adaptive organizing strategy was implemented through restructuring the organizational system, strengthening work coordination, and assigning more flexible tasks according to the needs of the madrasah. The principal played an important role in building communication, cooperation, and motivation among teachers and staff in facing organizational changes. Supporting factors included communicative leadership and a cooperative work culture, while the inhibiting factors were limited technology utilization and an ineffective performance evaluation system. Therefore, the adaptive organizing strategy was able to help the madrasah improve the effectiveness of educational management in a more responsive and directed manner.